SOCIOLOGICAL ASSESSMENT OF LOCAL GOVERNMENT INSTITUTES IN STAVROPOL REGION - Anna Nikolaevna Shmatova (Вестник Северо-Кавказского федерального университета, 2022)
The article presents the results of a sociological survey (public opinion poll) regarding the specific features of the local self-government institute functioning. It shows the attitude among the population towards the local self-government bodies, and offers an evaluation of the trust to the local government; there is also a view on the priority of the objectives set by the local self-government, as seen by the public.